Penerapan Komunikasi Media Massa dalam Mempromosikan Layanan Pernikahan di KUA Sunggal - Farid, Ahmad Salman (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2023)
This study examines mass media communication activities carried out by the Office of Religious Affairs (KUA) of Sunggal District in Deli Serdang Regency in promoting marriage services to the surrounding Muslim community. The implementation of KUA's duties in providing the best service to Muslim audiences should be supported by mass media instruments that explain the processes, procedures, and administrative matters that are the success of marriage in Islam. Adopting descriptive qualitative methods in this study look at the current situation and condition of marriage services at KUA Sunggal so that natural objects can provide a detailed description of the application of mass media communication in it. The data were then obtained by observation, in-depth interviews with informants from the Head of KUA and extension workers as well as official documentation on all matters relating to the object of research. The results of this study found that the role of mass media communication was still weak so efforts were needed and real actions in revitalizing, upgrading, and adjusting to publicity to the public in the era of technological progress 5.0 in the KUA work area, Sunggal District.